Effectiveness of in situ P-wave measurements in monuments: examples from Greece (Journal of Nepal Geological Society, 2000)
P and S wave velocities can be used for both in situ and laboratory measurements of stones. These methods are used for studying such properties as mechanical anisotropy and modulus of elasticity. In this paper, the P-wave velocities were used for the estimation of the depth of weathered or artificially consolidated layers as well as the depth of cracks developed at the surface of the building stone. This estimation was made in relation to the lithology and texture of the materials, given that in many cases different lithological data create similar diagrams. All tests were carried out on representative monuments in Greece.